More news tomorrow a novel - Shreve, Susan 1939- (W.W. Norton & Company, 2019)
On the morning of her seventieth birthday, Georgianna Grove receives an unexpected letter that calls her back to Missing Lake, Wisconsin, where her mother was murdered sixty- six years earlier. Georgie's father had confessed to the murder the next morning and was carted off to a state penitentiary. Haunted by the night that took both her parents away and determined to unearth the truth, Georgie takes her reluctant family on what will become a dangerous canoe trip up the swollen Bone River to return to Missing Lake. --